Comparative Evaluation of Physical and Mechanical Characteristics of Composite facing Materials "Ceramage" and "Ultraglass" - V. Tscymbalystov, Alexander; A. Kopytov Roman I. Asadov, Alexander; V. Kapranov, Valentina; P Ryzhova, Irina; ., . (International Journal of Engineering and Technology, 2018)
In the oral cavity, mechanical loading and exposure to temperature leads to deformation of the frameworks of fixed prostheses and lining materials ensuring the proper level of their aesthetics. The increase of the isotropy of the material of the framework of a fixed prosthesis and the material that is facing it is one of the urgent problems in the field of orthopedic dentistry. In this paper, the linear thermal expansion coefficients (LTEC) of the facing materials â€œCeramage Opaque Dentinâ€, â€œCeramage Incisalâ€, produced by the Japanese company â€œShofuâ€, and those of â€œUltraGlassâ€ of the Russian firm â€œVladMiVaâ€ were studied. The values of LTEC of facing materials were correlated with LTEC of cobalt-chromium alloy, used for making the frameworks of fixed prostheses. A comparative evaluation of the compressive strength, flexural strength, and modulus of elasticity of the specified composite materials used for facing the frameworks of fixed prostheses was also carried out.Â Â